2022
DOI: 10.1016/j.isci.2022.103743
|View full text |Cite
|
Sign up to set email alerts
|

Immunity to SARS-CoV-2 up to 15 months after infection

Abstract: Information concerning the longevity of immunity to SARS-CoV-2 following natural infection may have considerable implications for durability of immunity induced by vaccines. Here, we monitored the SARS-CoV-2 specific immune response in COVID-19 patients followed up to 15 months after symptoms onset. Following a peak at day 15-28 postinfection, the IgG antibody response and plasma neutralizing titers gradually decreased over time but stabilized after 6 months. Compared to G614, plasma neutralizing titers were m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
48
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 68 publications
10
48
0
2
Order By: Relevance
“…Our results regarding outpatients support those previous findings and are consistent with the waning of IgM and stabilization of IgA and IgG titers of still positive neutralizing titers found after several months postsymptoms onset (64,(68)(69)(70). Interestingly, Marcotte H et al have found a similar seroprevalence of IgG titers over time, even up to 15 months after infection (67), which are in the same trend of results obtained by our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results regarding outpatients support those previous findings and are consistent with the waning of IgM and stabilization of IgA and IgG titers of still positive neutralizing titers found after several months postsymptoms onset (64,(68)(69)(70). Interestingly, Marcotte H et al have found a similar seroprevalence of IgG titers over time, even up to 15 months after infection (67), which are in the same trend of results obtained by our study.…”
Section: Discussionsupporting
confidence: 93%
“…The relevance of this new information is highlighted if the limited scope of prophylactic vaccination efforts in developing countries is taken in count (62). For instance, regarding the extent of longterm responses, even without segregation of individuals due to the severity of their COVID-19 symptoms, it has been shown that the majority of SARS-CoV-2 infected individuals develop serum Abs that last for several months (63)(64)(65), even beyond a year after infection (66,67). Our results regarding outpatients support those previous findings and are consistent with the waning of IgM and stabilization of IgA and IgG titers of still positive neutralizing titers found after several months postsymptoms onset (64,(68)(69)(70).…”
Section: Discussionmentioning
confidence: 99%
“…CD4+ T cells can be detected as early as day 2-4 after the onset of COVID-19 symptoms [4]. Marcotte et al (2021) found that the number of S-specific T cells producing IFN-γ reach peak values between 3 and 6 months and persist for up to 15 months [62].…”
Section: Cellular Immune Response In Covid-19mentioning
confidence: 99%
“…Neutralizing antibodies become detectable within 7–15 days of symptom onset and correlate with IgG levels [ 89 , 91 , 92 ]. Longitudinal studies have indicated that IgG levels peak between 3 and 7 weeks post-symptom onset; while levels subsequently decline, IgG may remain detectable for the duration of follow-up, which can be up to 10–15 months in some studies [ 92 , 93 , 94 , 95 , 96 ]. Loss of detectable antibodies (seroreversion) in a small proportion of patients after follow-up periods between 3 and 15 months has been reported, primarily in patients with mild or asymptomatic infection [ 95 , 96 , 97 , 98 , 99 ].…”
Section: Sars-cov-2: Implications For Blood Safety and Sufficiencymentioning
confidence: 99%